A comparison of Canadian and Belgian youth sport participation profiles. - Taks, Marijke; Stevens, Julie A; Scheerder, Jeroen; Lathrop, Anna H; Bradish, Cheri L (Université d'Ottawa | University of Ottawa, 2019)
In Canada, leisure time sport activities for youth are mainly offered through extracurricular programs within the school system, while a club system dominates in Belgium. These differences in sport delivery systems may affect opportunities for youth to participate in sport. Data on sport participation and socio-cultural background variables were collected from a national representative sample of Canadian adolescents (grades 9 to 12) and a representative sample of Flemish high school students (grades 7 to 12). Canadian youth showed higher levels of sport involvement and a stronger preference for team sports. The Canadian results reinforce the importance of parental influence on your sport participation, especially the father, whereas the Flemish results indicate a persistent social stratification in club participation based on age, sex, and parental education level. The school system as main supplier for leisure time sport activities can explain the lower level of segregation in sport participation among Canadian youth.
Keywords: Club sport; Cross-cultural analysis; Parental involvement; School sport; Social stratification